Proceso de nómina en la Empresa Futurcorp S. A. del Cantón Puebloviejo. - Oquendo Caamaño, Eliana Rosely (2022)
Futurcorp SA is an Ecuadorian company established on March 16, 1992 located in the Puebloviejo canton of the province of Los Ríos, which is dedicated to the production and marketing of puree, flakes and powder, using bananas as the main product. For information of the current administration of the processes that are executed and to define the shortcomings and pretend to verify if their concepts are properly applied, which allows them to manage efficiently and productively, for this reason in the company surveys and interviews were carried out with the staff that works in the organization, whose results were, to develop the payroll processes and functions that are directed to the administrative area of the company, in reference to its inefficient management of personnel hiring, salary payments and liquidations since there is the absence of a manual of procedures and controls in the form of work of the employees who work in it and that puts the production at risk company productivity.